An Asian viewpoint on the use of vitamin D and calcium in osteoporosis treatment: physician and patient attitudes and beliefs. - Chan, S.P.; Scott, B.B.; Sen, S.S. (BioMed Central, 2010)
There is generally suboptimal appreciation by both physicians and patients of the importance of vitamin D and calcium for maintenance of bone health as reflected in the low number of patients who reported regularly taking these supplements. Recognition of this problem should translate to appropriate action to improve education for both physicians and patients, with a goal to increase use of these supplements among Asian patients with osteoporosis.